Global food security in the context of COVID-19: A scenario-based exploratory analysis. (October 2020) - Udmale, Parmeshwar; Pal, Indrajit; Szabo, Sylvia; Pramanik, Malay; Large, Andy
Abstract: This study highlights the major players in the global food balance, potential implications of COVID-19 on global food supply, and SDG-2 (zero hunger). It found that developing countries, fifteen from Africa followed by ten from Latin America, six from Oceania, and four from Asia, are the most vulnerable to changes cereal supply shocks. It concludes that the current pandemic is likely to cause transitory food insecurity across such vulnerable countries. The effects of the pandemic on food security (SDG-2) may persist longer as a combined effect of economic slowdown and increase in poverty, limiting food supply and access beyond 2020.